2011
DOI: 10.4103/0976-500x.77104
|View full text |Cite
|
Sign up to set email alerts
|

Adverse drug reactions of nonsteroidal antiinflammatory drugs in orthopedic patients

Abstract: Objectives:To identify the ADRs due to NSAIDs and to know how to monitor the drug’s effect.Materials and Methods:A descriptive study was undertaken in the Orthopedic Outpatients Department of a tertiary care teaching hospital. Hundred patients were enrolled in this study to observe the risk of adverse drug reactions (ADRs) due to NSAIDs. All the ADRs were further analyzed in relation to age and sex, type of drug and its pattern. Probability scale was used for the causality assessment of the ADRs.Results:26% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 20 publications
1
33
1
2
Order By: Relevance
“…This is of serious concern as the risk of gastrointestinal erosion and hemorrhage increases even further with the concomitant use of NSAIDs and corticosteroids. [27] Also drugs such as vitamin B complex (2, 10.5%), cod liver oil, Sulpfadoxine-pyrimetamine, Salbutamol and Ferrous sulphate (1, 5.3%) and multivitamin (12, 63.2%) not indicated for analgesia were found to be included in some of the single doses. This gross irrational combination of drugs may be indicative of the fact that shop attendants in the community pharmacies and PMSs in this study area lack the basic concept of pain and its pharmacological management.…”
Section: Discussionmentioning
confidence: 99%
“…This is of serious concern as the risk of gastrointestinal erosion and hemorrhage increases even further with the concomitant use of NSAIDs and corticosteroids. [27] Also drugs such as vitamin B complex (2, 10.5%), cod liver oil, Sulpfadoxine-pyrimetamine, Salbutamol and Ferrous sulphate (1, 5.3%) and multivitamin (12, 63.2%) not indicated for analgesia were found to be included in some of the single doses. This gross irrational combination of drugs may be indicative of the fact that shop attendants in the community pharmacies and PMSs in this study area lack the basic concept of pain and its pharmacological management.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it has to be considered superior to other types of treatments that need more complicated, time-consuming, and expensive procedures. Considering the fact that pharmacological treatments for chronic pain are discouraged by practically all guidelines because of either potential side effects, as with NSAIDs [50], or the potential for dependence with other substances [51, 52], uncomplicated alternatives such as PPT are most welcome. Our data show that PPT is effective and uncomplicated, as we had no dropouts due to adverse events or other complications.…”
Section: Discussionmentioning
confidence: 99%
“…However, the reason may be because, it has been established that continuous therapy for a long time more than 28 days, may put the patient at a higher risk of ADR, drug-interaction and medication non-adherence. 5,8 In many reported cases, the gastrointestinal (GI) complications related to NSAIDs use was four times higher when compared to non-users. 9,10 Furthermore, findings of the current study has also indicated that patients on medications for management of chronic underlying illness are among the frequent users of NSAIDs.…”
Section: Drug Utilization Pattern Of Nsaidsmentioning
confidence: 99%
“…Despite the widespread utilization and effectivenesss, the use of NSAIDs is associated with adverse drug reactions (ADR) such as gastro-intestinal (GI) complications, leading to hospitalization and deterioration of disease conditions. 4,5 A report has shown that, Diclofenac Sodium, a sub-class of NSAIDs was among the top three drugs most commonly implicated in ADR based on the Malaysian Adverse Drug reaction Advisory Committee (MADRAC) report in 2008.r. Another study has indi-cated that the risk of serious GI complications in NSAID's users is almost four times higher than nonusers.…”
Section: 3mentioning
confidence: 99%